Legal Review of The Legality of Authentic Deeds and Private Deeds According to Law No. 2 of 2014 Concerning the Position of Notary in Land and Building Lease Agreements - Erwan, Puti Annisa; Citra, Helfira (Jurnal Ilmiah Ekotrans & Erudisi, 2025)
This study analyzes the legality and evidentiary weight of authentic and private deeds in land and building lease contracts under Indonesia’s Law No. 2 of 2014 on the Notary’s Position. In civil practice, authentic deeds executed by or before a notary have conclusive probative force and afford more substantial legal certainty. Private deeds, made without the authorization of authorized officials, are weaker, especially when disputes arise. Using a normative legal method, statutory analysis, and illustrative cases, the research draws on primary, secondary, and tertiary sources, including the Civil Code, related regulations, and notarial scholarship. It asks: (1) What is the evidentiary power of private versus authentic deeds in lease disputes? (2) What legal consequences flow to the parties when a lease is drafted as a private deed rather than an authentic deed? Authentic deeds better secure certainty, narrow the room for conflict, and provide more effective protection. Private deeds are more flexible and easier to create but carry a higher litigation risk, particularly if a party denies consent. The study recommends using authentic deeds for leases and urges clearer policies on recognizing and proving private deeds to enhance public understanding and transparency.